The outward direct Investment from CEECs: Can their firms compete in the global market - Andreja Jaklič; Marjan Svetličič (Journal for East European Management Studies, 2003)
The article analyses the recent emergence of multinational companies (MNCs) from Central and Eastern European countries (CEECs), especially the Czech Republic, Estonia, Hungary, Poland, and Slovenia. The majority of MNCs from CEECs concentrate their activity regionally, though some global MNCs also exist. Geographical allocation of outward FDI gives evidence that physical distance, cultural nearness and historical ties are relevant in deciding where to invest. Past experience matters a lot, but at least equally important are ambitious plans and constant upgrading of advantages. MNCs from CEECs experienced positive net effect of outward FDI, such as improved market positions, growth of export, higher efficiency, which also enhances their competitive advantages. – – Der Artikel analysiert das jüngste Auftauchen von multinationalen Unternehmen (MNCs) aus mittel- und ostmitteleuropäischen Ländern(CEECs), insbesondere der Tschechischen Republik, Estland, Ungarn, Polen und Slowenien. Die Mehrheit der MNCs aus den CEECs sind vorwiegend regional aktiv, sie sind aber auch global existent. Die geographische Zuordnung von FDI beweisen, das die physische Entfernung, kulturelle Nähe und historische Verbindungen relevant für die Entscheidung der Investition sind. Frühere Erfahrungen sind wichtig, mindestens genauso wichtig sind ehrgeizige Pläne und das konstante Verbesssern von Vorteilen. MNCs von CEECs erfuhren einen positiven Nettoeffekt von FDI wie verbesserte Marktpositionen, Exportwachstum, höhere Effizien, die auch ihre Wettbewerbsvorteile erhöht.
Keywords: 650; Outward foreign direct investment; multinational companies; internationalisation strategies; competitive advantages